The Role of Advocate Communication in Handling Criminal Cases for the Underprivileged Community in the Context of Islamic Law - Sulfitrah; Marilang; Hamzah Hasan (Jurnal Mercusuar, 2022)
through Islamic Law. The research utilized is field research (qualitative) with an Islamic law approach. The population includes all lawyers in Makassar, all underprivileged communities in Makassar, and all judges and prosecutors in Makassar. The research sample consists of 10 lawyers from YLBH Justice RM, 10 community members, and 5 judges and prosecutors from the District Court of Makassar. Data collection methods used are observation, interviews, and documentation. The analysis encompasses data editing, classification, verification, data analysis, and conclusion drawing. The results of this research indicate that: 1. The substantive role of lawyers in handling criminal cases for underprivileged communities viewed through Islamic Law is as legal companions who assist communities in clarifying the law to the police, prosecutors, and judges, aiding in upholding justice and not charging clients. The implications of this thesis serve as a means to maintain the professionalism of lawyers in performing their duties under various conditions, even without charging fees from the community. In the process of handling criminal cases, communities are obliged to follow all existing legal procedures with transparency and honesty.